Baseline total lesion glycolysis combined with interim positron emission tomography‐computed tomography is a robust predictor of outcome in patients with peripheral T‐cell lymphoma. (18th June 2020) - Kitadate, Akihiro; Narita, Kentaro; Fukumoto, Kouta; Terao, Toshiki; Tsushima, Takafumi; Kobayashi, Hiroki; Abe, Yoshiaki; Miura, Daisuke; Takeuchi, Masami; Machida, Youichi; Matsue, Kosei
Abstract: Background: Peripheral T‐cell lymphoma (PTCL) represents a heterogeneous and rare subgroup of aggressive lymphomas that generally demonstrate poor clinical outcomes with conventional treatment. Since the prognosis of PTCL is heterogeneous, more accurate risk assessment, and risk‐adapted treatment strategies are required. In this study, we examined whether interim positron emission tomography (iPET)‐computed tomography (PET/CT) results can be combined with baseline volume‐based metabolic assessments including total metabolic tumor volume (TMTV) and total lesion glycolysis (TLG) for risk stratification in PTCL. Methods: The data of 63 patients with nodal PTCL, who had analyzable baseline PET/CT and iPET, were retrospectively reviewed. We calculated the baseline TMTV and TLG values. All iPET responses were analyzed using the Deauville 5‐point scale. Results: On univariate analysis, a prognostic index for PTCL (PIT) higher than 2 (hazard ratio [HR], 2.03; P = .026), high TMTV (>389 cm 3 ; HR, 2.24; P = .01), high TLG (>875; HR, 3.77; P = .0005), and positive iPET (HR, 2.18; P = .009) were significantly associated with poorer progression‐free survival (PFS). On multivariate analysis, only high TLG and positive iPET independently predicted both poorer overall survival (OS) and PFS. A model combining TLG and iPET showed that patients with low TLG and negative iPET had superior outcomes, with a 5‐year PFS and OS of 72% and 90%, respectively. Conversely, both 5‐year PFS and OS for those with high TLG and positive iPET were 0%. Conclusions: In summary, TLG combined with iPET predicted survival in PTCL more accurately. This information may help in the development of risk‐adapted treatment strategies for PTCL. Abstract : Recently, volume‐based positron emission tomography‐computed tomography (PET/CT) assessments such as total metabolic tumor volume (TMTV) and tumor lesion glycolysis (TLG) have been reported to be useful prognostic indicators for various cancers. In this study, we found that baseline TLG has stronger prognostic potential than baseline TMTV, and interim PET/CT response can be combined with TLG to improve risk stratification in peripheral T‐cell lymphoma.